2019
DOI: 10.1136/jnnp-2018-319657
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic fast-tracking: enhanced multimodal integration in functional neurological disorder

Abstract: ObjectiveSome individuals with functional neurological disorder (FND) exhibit motor and affective disturbances, along with limbic hyper-reactivity and enhanced motor-limbic connectivity. Given that the multimodal integration network (insula, dorsal cingulate, temporoparietal junction (TPJ)) is implicated in convergent sensorimotor, affective and interoceptive processing, we hypothesised that patients with FND would exhibit altered motor and amygdalar resting-state propagation to this network. Patient-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 55 publications
6
56
0
1
Order By: Relevance
“…Using the fMRI task-defined left hippocampus and left and right amygdala ROIs as seeds in rs-FC analysis showed significant differences in right amygdala functional connectivity to the left precentral and the left inferior/middle frontal gyri that was increased in PNES compared to HCs. The observed involvement of right amygdala is consistent with other structural and functional connectivity studies of patients with PNES/FNDs that investigated amygdala connectivity (Diez et al, 2019; Hernando et al, 2015; Morris et al, 2017; Voon et al, 2010; Wegrzyk et al, 2018). However, in our study, greater rs-FC between emotion (amygdala) and motor control regions (precentral gyrus) in PNES suggests potential underlying pathophysiology of PNES that present with major motor symptoms, which was characteristic of our sample (all participants had major motor events).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using the fMRI task-defined left hippocampus and left and right amygdala ROIs as seeds in rs-FC analysis showed significant differences in right amygdala functional connectivity to the left precentral and the left inferior/middle frontal gyri that was increased in PNES compared to HCs. The observed involvement of right amygdala is consistent with other structural and functional connectivity studies of patients with PNES/FNDs that investigated amygdala connectivity (Diez et al, 2019; Hernando et al, 2015; Morris et al, 2017; Voon et al, 2010; Wegrzyk et al, 2018). However, in our study, greater rs-FC between emotion (amygdala) and motor control regions (precentral gyrus) in PNES suggests potential underlying pathophysiology of PNES that present with major motor symptoms, which was characteristic of our sample (all participants had major motor events).…”
Section: Discussionsupporting
confidence: 89%
“…Functional neurological disorders (FND) including PNES are thought to be a network disorder with clinical symptomatology and phenotypic expression dependent on which node of the network is involved in the generation and maintenance of the disorder (Szaflarski and LaFrance, 2018). Functional MRI (fMRI) studies have consistently shown resting state functional connectivity (rs-FC) for emotion-regulation and motor-control regions to be stronger in patients with PNES (Ding et al, 2013; Szaflarski et al, 2018; van der Kruijs et al, 2012) and in FND (Diez et al, 2019; Morris et al, 2017; Wegrzyk et al, 2018) compared to HCs. Less consistent findings have been shown in the differential fMRI response to emotional/negative stimuli between HCs and persons with conversion disorder/FND including PNES.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of the DMN in PD‐DLB visual hallucinations is supported by many studies (Table ), these mechanisms have not been investigated in SFDs associated with PD‐DLB. However, some fMRI studies of SFDs in patients without associated synucleinopathies have shown increased activity or connectivity in the cingulate cortex and the PCC, thereby providing preliminary functional support for the idea that the same mechanisms can play a role in PD‐DLB‐associated SFDs.…”
Section: Anatomical Pathophysiological Overlaps and Mechanismsmentioning
confidence: 94%
“…7 Recent studies of PNES and other FNSDs have begun to elucidate the neural basis for these disruptions by examining corresponding changes in volume and function of brain regions, [8][9][10][11] yet changes in the structural connections of these brain networks remains less well understood. 12 Determining network functionality and connectivity that underlies PNES may increase our ability to develop new therapies to target-specific parts of the network that yield greater treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%